2012
DOI: 10.1016/j.yjmcc.2012.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of adult cardiac function requires the chromatin factor Asxl2

Abstract: During development and differentiation, cell type-specific chromatin configurations are set up to facilitate cell type-specific gene expression. Defects in the establishment or the maintenance of the correct chromatin configuration have been associated with diseases ranging from leukemia to muscular dystrophy. The heart expresses many chromatin factors, and we are only beginning to understand their roles in heart development and function. We have previously shown that the chromatin regulator Asxl2 is highly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Recently, Lai et al 8. showed that deletion of Asxl2 led to reduced global H3K27me3 levels in heart cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lai et al 8. showed that deletion of Asxl2 led to reduced global H3K27me3 levels in heart cells.…”
Section: Discussionmentioning
confidence: 99%
“…Asxl1 loss leads to the development of myeloid malignancies in mice, which is associated with dysregulation of H3K27me3 (refs 6, 7). Lai et al 8. previously reported that ASXL2 regulates gene expression in the heart at cell-type and stage-specific manners.…”
mentioning
confidence: 99%
“…To confirm that murine ASXL2 is also associated with chromatin, we expressed FLAG-tagged ASXL2 in HEK293 cells and used biochemical fractionation [20] to separate chromatin-associated proteins from soluble nuclear proteins. Probing the fractions with either the anti-ASXL2 antibody KC17 [21] or with anti-FLAG antibody M2 (Sigma) detected ASXL2 predominantly in the chromatin fraction (Figure 1A). Similar results were obtained with endogenous ASXL2 in murine heart tissue (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…9 In addition, recent studies have expanded the complexity of regulatory determinants that participate in cardiac gene function, for example histone modifying proteins such as EZH2 and ASXL2 specify MHC gene expression in postnatal cardiac homeostasis. 10,11 Human homologs of Drosophila genes (Enhancer of zeste homolog 2 and Additional sex combs-like protein 2) EZH2 and ASXL2 are members of the Polycomb group (PcG) protein family implicated in maintaining gene repressive states by chromatin modification during later stages of heart development.…”
Section: Interplay Of Chromatin Modifications and Non-coding Rnas In mentioning
confidence: 99%
“…1). 11,63 DNase hypersensitive sites are also associated with MHC gene expression at various developmental stages of the heart. 64 Whatever the role of EZH2, showing its involvement in chromatin dependent association with ncRNA is the first step in revealing how MHC isoform expression is regulated in heart disease.…”
Section: Non-coding Rnas Connect Ezh2 With Chromatinmentioning
confidence: 99%